Impact of marriage on diagnosis and survival in patients with urological cancers - Hua Wang; Yong Zhao; Shifeng Feng; Guo Wei (Scientific Reports)
Abstract The protective role of marriage has been identified in various cancers, but its effect on the overall urological system remains unclear. Patients diagnosed with bladder cancer (BCa), renal cell carcinoma (RCC), and upper tract urothelial carcinoma (UTUC) were identified from the Surveillance, Epidemiology, and End Results (SEER) database. Patients were divided into married and unmarried groups based on their marital status. A binary multivariable logistic regression was used to explore the effect of marriage on the diagnosis of urological cancers. One-to-one propensity score matching (PSM) was employed to reduce baseline differences between the two groups. Multivariable Cox regression analysis and subgroup analysis were conducted to investigate the impact of marriage on cancer-specific survival (CSS). A total of 162,544 patients were included in the study, with a median follow-up period of 6.2 years (IQR 2.3–9.8 years). Among them, 104,706 (64.4%) were married, and 57,838 (35.6%) were unmarried. Married patients had a lower risk of being diagnosed with stage III/IV disease compared to unmarried patients (OR 0.94, 95% CI 0.92–0.96, p < 0.001), but this trend was only significant in BCa (OR 0.88, 95% CI 0.84–0.91, p < 0.001), but not in RCC (OR 0.98, 95% CI 0.94–1.01, p = 0.172) or UTUC (OR 1.03, 95% CI 0.95–1.12, p = 0.523). After PSM, 47,975 patients were included in each group, and marriage was found to be an independent protective prognostic factor for CSS (HR 0.81, 95% CI 0.79–0.83, p < 0.001), but this was not significant in UTUC (HR 0.95, 95% CI 0.88–1.03, p = 0.244). Across the entire urological system, marriage is an independent protective predictor for both diagnosis and survival, but the effect varies among different types of cancers.